PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSETS PADA PT BUMI SERPONG DAMAI TBK PERIODE 2014 – 2023 - Siti Farida; Rizka Wahyuni Amelia (Journal of Research and Publication Innovation, 2025)
This study aims to determine the partial and simultaneous effects of Current Ratio and Debt to Equity Ratio on Return on Assets at PT Bumi Serpong Damai Tbk for the period 2014-2023. The research method uses quantitative research methods, while the data used is secondary data in the form of financial statements of PT Bumi Serpong Damai, Tbk for the period 2014-2023. The analysis includes descriptive analysis, classical assumption tests, correlation coefficient, determination coefficient, simple linear regression analysis, multiple linear regression analysis, and hypothesis testing using t-test and F-test with SPSS version 25. The partial results show that Current Ratio has a t-count < t-table (-1.098 < 2.306) with a significant probability of 0.304 > 0.05, thus partially CR does not affect Return on Assets. Debt to Equity Ratio has a t-count > t-table (-4.745 > 2.306), with a significant probability of 0.001 < 0.05, thus partially Debt to Equity Ratio has a positive and significant effect on Return on Assets. The partial coefficient of determination of CR to ROA is 13.1%, while the partial coefficient of determination of DER to ROA is 73.8%. The simultaneous research results between CR and DER on ROA show an F-count > F-table (16.400 > 4.74) with a significant value of 0.002b < 0.05. Therefore, CR and DER simultaneously affect ROA. The coefficient of determination is 82.4%, which means that the independent variables consisting of Current Ratio and Debt to Equity Ratio affect Return on Assets. The remaining 17.6% is influenced by other variables not examined in this study.